Social Sciesce Considerations in the Management of Tropical Forest Zones of South East Asia - Henning, Daniel H. (Indian Forester, 1977)
Social science can be of great help in solving tropical forest management problems specially with the changing complexities and problems of sociotropical forest relationships. The policy changes of tropical forest management as well as their implementation needs study by the social sciences. Uncontrolled logging operations and unplanned human invasions and developments will mean the irreversible destruction of much of the tropical forests of South East Asia. Government can control this with the help of social sciences in cooperation with techno-scientific disciplines. Forest management organizations would do well to establish divisions of social sciences with professionally trained social scientists at various levels. Contributions or the interdisciplinary environmental approach towards the management of tropical forest zones would involve identification, articu1ation, and conflict analysis of human and societal values and behaviour for knowledge, problem solving, decision making and planning. Due to inter disciplinary approach several advantages such as: (a) Cross fertilization of idea; (b) Synthesis of microscopic/macroscopic viewpoints. (c) Personal Development and (d) solution of complex of problems would result. Social sciences should be included in ecosystetn inventions, surveys, and planning of tropical forests with more public participation in environtnental planing and decisions, including tropical forests. The social sciences could contribute knowledge, analysis, synthesis, and education. The management should recognize the potential uses (and values) of the tropical forest euviroament. The less obvious UBes and values (including non-economic and intengible one, of socio-tropical forest relationships need study and implementation under an interdisciplinary environmental approach with the utilization of the social sciences. Future economic benefits from tropical forests would not only come in terms of yields of commercially selected plant and tree species but utilization of wild life, better knowledge of pest control, understanding the productivity processes, water control, improved exploitation of timber resources, reservoirs of genetic material, etc, Social science personnel could he available from agencies such as universites, organizations, and research institutes concerned with tropical forests. Two possible working arrangements may be (a) a team of social scientists technoscientific specialists, and other expertise with all individuals under an "integretation" orientation throughout the study processes and (b) a social scientist with various supporting fields of training in other disciplines. The social sciences, under an ecological orientation and through cooperatiye activities with techno-scientific specialists, can provide a frame work. Social sciences could contribute to the study, management and public education for the preservation and protection of tropical forests for their own sake by society.